2018
DOI: 10.1021/jacs.8b05107
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom-Based Vanadium Oxide Catalysts Supported on Metal–Organic Frameworks: Selective Alcohol Oxidation and Structure–Activity Relationship

Abstract: We report the syntheses, structures, and oxidation catalytic activities of a single-atom-based vanadium oxide incorporated in two highly crystalline MOFs, Hf-MOF-808 and Zr-NU-1000. These vanadium catalysts were introduced by a postsynthetic metalation, and the resulting materials (Hf-MOF-808-V and Zr-NU-1000-V) were thoroughly characterized through a combination of analytic and spectroscopic techniques including single-crystal X-ray crystallography. Their catalytic properties were investigated using the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
189
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(195 citation statements)
references
References 45 publications
5
189
0
1
Order By: Relevance
“…[14c] Farha and co‐workers recently reported that vanadium oxide catalyst consisted of two highly crystalline MOFs with high porosity. In these MOFs, the single vanadium atoms were stabilized with different binding motifs on the metal oxide nodes . Wang and co‐workers recently applied a plasma strategy to directly form single CoO x species (CoO x –ZIF).…”
Section: Defects‐based Single Atomic Electrocatalystmentioning
confidence: 99%
“…[14c] Farha and co‐workers recently reported that vanadium oxide catalyst consisted of two highly crystalline MOFs with high porosity. In these MOFs, the single vanadium atoms were stabilized with different binding motifs on the metal oxide nodes . Wang and co‐workers recently applied a plasma strategy to directly form single CoO x species (CoO x –ZIF).…”
Section: Defects‐based Single Atomic Electrocatalystmentioning
confidence: 99%
“…These results open new avenues in the design of SACs [19] and expand the understanding of the low-temperature WGSR mechanism. These results open new avenues in the design of SACs [19] and expand the understanding of the low-temperature WGSR mechanism.…”
Section: Angewandte Chemiementioning
confidence: 75%
“…In summary,Pt 1 1+ coordinated to and stabilized by awater cluster in aMOF can be obtained on agram-scale and used as an efficient catalyst for the low-temperature WGSR and ad ouble water attack mechanism to give CO 2 ,w here both oxygen atoms come from water. These results open new avenues in the design of SACs [19] and expand the understanding of the low-temperature WGSR mechanism. Figure 5.…”
Section: Angewandte Chemiementioning
confidence: 75%
“…These materials are useful in catalysis, separations, sensors, and recently, as non-toxic vehicles for drug delivery. [19][20][21][22][23][24][25][26][27] We and others have described a specific type of MOF called ZIF-8, 28, 29 composed exclusively of zinc metals interconnected by methylimidazole ligands, that crystallize "biomimetically" on a variety of biomacromolecules including soluble proteins, polysaccharides, viruses, and whole cells. [30][31][32][33][34][35][36] For this study, we used CFT073, a model urosepsis strain of UPEC frequently employed in the development of new vaccines.…”
Section: Zif Encapsulates and Inactivates Upec Urosepsis Strain Cft073mentioning
confidence: 99%